Development of the Agrarian Sector of the Ukrainian Economy: Forecasts and Prospects - Kolesnikov, S.; Mishura, V. (Економічний вісник Донбасу, 2019)
In the article the modern problems of development of agrarian sector of economy of Ukraine in the conditions of institutional changes are revealed. The development of the agrarian sphere of the country in the context of institutional changes is analyzed. Prospects for the development of the agricultural sector of the national economy have been determined, taking into account the existing risks and possible options for public policy.
The correlation analysis of farms and non-farms for the period from 2012 to 2018 is conducted. Thus, the dependence of Y on X was studied. In the specification step, a pairwise linear regression was chosen. It estimated its least squares parameters. The statistical significance of the equation is verified using the Fisher coefficient and determination. Only 10.35% of the total variability of Y is found to be explained by the change in X. The statistical significance of the model is due to the small sample size and the influence of other factors on the effective factor U. It is proved that to ensure a rational level of compliance of agricultural producers with agro-technological requirements it is necessary to take a set of measures, in particular: to introduce a favorable regime of import of imported mineral fertilizers and means; introduce economic incentives for land owners, land users and land tenants to increase soil fertility and improve their economic condition. У статті виявлено сучасні проблеми розвитку аграрного сектору економіки України в умовах інституційних змін. Проаналізовано розвиток аграрної сфери країни в контексті інституційних перетворень. Визначено перспективи розвитку аграрного сектору національної економіки з урахуванням наявних ризиків і можливих варіантів державної політики. Проведено кореляційний аналіз фермерських і нефермерських господарств за період з 2012 по 2018 рік. Таким чином, вивчена залежність Y від X. На етапі специфікації була обрана парна лінійна регресія. Оцінено її параметри методом найменших квадратів. Статистична значимість рівняння перевірена за допомогою коефіцієнта детермінації й критерію Фішера. Встановлено, що в досліджуваній ситуації тільки 10.35% загальної варіабельності Y пояснюється зміною X. Статистична значимість моделі обумовлена невеликим обсягом вибірки й впливом інших факторів на результативний фактор U. Доведено, що для забезпечення раціонального рівня дотримання сільгосптоваровиробниками агротехнологічних вимог необхідно вжити комплекс заходів, зокрема: запровадити сприятливий режим ввезення імпортованих мінеральних добрив і засобів захисту рослин; запровадити економічне стимулювання власників землі, землекористувачів та орендарів земельних ділянок за підвищення родючості ґрунтів і поліпшення їх економічного стану. В статье выявлены современные проблемы развития аграрного сектора экономики Украины в условиях институционных изменений. Проанализировано развитие аграрной сферы страны в контексте институционных преобразований. Определены перспективы развития аграрного сектора национальной экономики с учетом имеющихся рисков и возможных вариантов государственной политики. Проведен корреляционный анализ фермерских и нефермерских хозяйств за период с 2012 по 2018 год. Таким образом, изучена зависимость Y от X. На этапе спецификации была избрана парная линейная регрессия. Оценены ее параметры методом наименьших квадратов. Статистическая значимость уравнения проверена с помощью коэффициента детерминации и критерия Фишера. Установлено, что в исследуемой ситуации только 10,35% общей вариабельности Y объясняется изменением X. Статистическая значимость модели обусловлена небольшим объемом выборки и влиянием других факторов на результативный фактор U. Доказано, что для обеспечения рационального уровня соблюдения сельскохозяйственными товаропроизводителями агротехнологических требований необходимо применить комплекс мероприятий, в частности: ввести благоприятный режим ввоза импортированных минеральных удобрений и средств защиты растений; ввести экономическое стимулирование владельцев земли, землепользователей и арендаторов земельных участков за повышение плодородия грунтов и улучшение их экономического состояния.